Penolakan Indonesia dalam Meratifikasi Konvensi UNESCO Tahun 2001 tentang Perlindungan Cagar Budaya Bawah Air - Rizky Widiasa (Universitas Diponegoro, 2021)
The 2001 UNESCO Convention on the Protection of Underwater Cultural Heritage houses countries that have a vision and mission to protect underwater relics. By emphasizing the aspects of cooperation based on notification and reporting, this convention normatively measures the implementation of programs that depend on the capabilities of its member countries as a regime for archaeological relics preservation that sank on the seabed. Until now the Indonesian government has not ratified the convention and even tends to reject it. In fact, Indonesia as an archipelagic country has the responsibility to preserve the legacy of underwater cultural heritage in its sea area. This article analyzes the strategic decision of the Indonesian government to delay ratifying the 2001 UNESCO Convention on the Protection of Underwater Cultural Heritage. The theory of state participation in international organizations suggests that a convention requires commitment from the parties involved to solve global problems. Ratification is needed by the state to be bound by the convention to achieve national interests. In the end the decision not to join the convention was due to its impact which did not provide benefits for the state.